Giant gastric leiomyoma excision using endoscopic submucosal dissection with dental floss clip traction technique: a case report - Jiwen Deng; Zhaohui Liu; Dayong Sun (Journal of International Medical Research)
For gastric leiomyomas measuring ≥5 cm, endoscopic resection is necessary. The larger size of these tumors significantly impairs the resection field of view, increasing the risk of intraoperative bleeding and perforation and potentially leading to incomplete tumor removal. The combination of dental floss and tissue clip traction techniques is commonly used for resecting mucosal lesions but is rarely reported for submucosal tumors. We recently completed a case of endoscopic resection of a giant gastric leiomyoma in the body of the stomach, approximately 7 cm in length, using endoscopic submucosal dissection with dental floss clip traction. The dissection was carefully controlled within the muscularis propria layer, avoiding damage to the serosa. No bleeding or perforation occurred. A special technique was employed to avoid damage to the muscle layer. By combining this technique with tissue forceps, better traction stability may have been achieved. During the traction process, slight tension was consistently maintained between the swelling and the muscle layer, preventing perforation due to traction. The resection field remained clear throughout the procedure, which lasted 50 minutes in total. The final outcome was satisfactory. This method may be worthy of clinical application.